Pedagogical Conditions for the Integration of Digital Technologies into Students’ Art Education - Han, Bingjie; Bayalieva, Aisulu; Zhang, Chongyang; Yu, Jie; Karabalaeva, Gulmira (Harmonia: Journal of Arts Research and Education, 2026)
The study aimed to examine the implementation of digital tools in the artistic education process in China and Kyrgyzstan, determine their impact on the quality of the educational process, and assess their role in shaping students’ creative competencies. The study analyzed educational programs from leading universities in both countries, the digital tools actively used in education, and peer-reviewed scientific sources. The analysis included a review of educational platforms, software, and technologies applied in higher education institutions in China and Kyrgyzstan. A model of optimal pedagogical conditions for integrating digital tools into art education in Kyrgyzstan was developed, which could significantly improve the quality of education and accelerate its development in this field. The findings indicate noticeable differences in how the two countries approach the implementation of digital technologies in art education. In China, selected institutions make broader use of tools such as virtual and augmented reality, AI-based platforms, and online educational platforms that support access to external learning resources. In Kyrgyzstan, digital technology integration is more closely associated with the adoption of accessible tools and the integration of cultural heritage into student projects. Programs such as graphic editors and collaborative platforms support the creation of works reflecting national cultural values, although the overall scale and technological complexity of implementation remain more limited.